2022
DOI: 10.3390/nano12050828
|View full text |Cite
|
Sign up to set email alerts
|

Safety Assessment of 2D MXenes: In Vitro and In Vivo

Abstract: MXenes, representing a new class of two-dimensional nanomaterial, have attracted intense interest in a variety of fields as supercapacitors, catalysts, and sensors, and in biomedicine. The assessment of the safety of MXenes and related materials in biological systems is thus an issue that requires significant attention. In this review, the toxic effects of MXenes and their derivatives are summarized through the discussion of current research into their behaviors in mammalian cells, animals and plants. Numerous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 66 publications
1
19
0
Order By: Relevance
“…There are several comprehensive reviews reporting the recent progress on the cytotoxicity evaluation of MXenes. [234][235][236] Some reports attributed the cell cytotoxicity of MXenes to the oxidative stress induced by the generated ROS. On the other hand, there are other studies reporting higher cytotoxicity of MAX phases f-i) Antibacterial efficiency of MXene/cellulose and GO/cellulose membranes against E. coli and S. aureus.…”
Section: Cytotoxicity and Environmental Impacts Of Mxenesmentioning
confidence: 99%
“…There are several comprehensive reviews reporting the recent progress on the cytotoxicity evaluation of MXenes. [234][235][236] Some reports attributed the cell cytotoxicity of MXenes to the oxidative stress induced by the generated ROS. On the other hand, there are other studies reporting higher cytotoxicity of MAX phases f-i) Antibacterial efficiency of MXene/cellulose and GO/cellulose membranes against E. coli and S. aureus.…”
Section: Cytotoxicity and Environmental Impacts Of Mxenesmentioning
confidence: 99%
“…However, this controversy about toxicity is generally associated with the material’s dose, mode of exposure, cell type and specific MXene types. It has also been reported that MXene stability is a major concern, as degradation of MXene may produce toxic byproducts with potential impacts on the ecosystem [ 70 ]. Going further, MXene is prone to oxidation, and it is unclear where this issue would limit the MXene prospects [ 71 ].…”
Section: Limitations Of Mxene Modified Membranesmentioning
confidence: 99%
“…81 MXenes hold a unique combination of various promising features such as the presence of redox-active sites, high anchoring capacity for biomaterials and rapid transduction of electrical and optical signals. 91,92 Such factors play a pivotal role to realize ultrasensitive biosensors with high specicity and signicantly low limits of detection (LOD). MXenes can host several target-specic biomolecules (e.g., antibodies, enzymes, aptamers, etc.…”
Section: Mxenes Supremacymentioning
confidence: 99%